Achromobacter: an emerging nosocomial pathogen - Pandey, Kxitiza; Nautiyal, Sulekha (International Journal of Research in Medical Sciences, 2019)
Background: Achromobacter is a ubiquitous, non-fermenting, Gram-negative bacterium that lives in soil and aquatic environments. In recent years, many studies have shown its potential as opportunistic pathogen. It can colonize various items used in hospital and can survive various disinfectants. The infections get complicated due to its vast spectrum of intrinsic and extrinsic resistance to antimicrobial agents and disinfectants. Achromobacter spp. is an emerging pathogen and is becoming a reservoir for horizontal genetic transfer elements involved in spreading antibiotic resistance. This study was conducted to assess the extent of the Achromobacter related infection in our hospital setting and to set a baseline for future studies. Methods: This study was conducted over a period of one year (January to December 2018) in our tertiary care hospital. All specimens submitted for aerobic culture and sensitivity were analyzed and the bacterial identification and antibiotic sensitivity of the isolates was carried out using automated method (Vitek 2 Compact, bioMerieux). Results: Achromobacter species was reported from 0.46% (63/13831) specimens, 40% of them were isolated from suction tips. Achromobacter denitrificans amounted for 47/63 (74.6%) while Achromobacter xylosoxidans was identified in 16/63 (25.4%). Conclusions: Studying the organisms in order to observe their changing trends